Methodology of effective structural identification of complex dynamic systems - Блохін, Л. М.; Рудюк Г. I.; Сущенко, О. А.; Калініченко, В. В. (Proceedings of National Aviation University (archive), 2002)
Features of structural identification of models of dynamics of multidimensional objects are considered. The algorithms for determining the transfer functions of the identification object and the filter that generates the dynamic characteristics of the perturbation are proposed, and the method for determining the dynamic properties of a linear stationary dynamic object